2012
DOI: 10.1038/labinvest.2011.199
|View full text |Cite
|
Sign up to set email alerts
|

SSeCKS sequesters cyclin D1 in glomerular parietal epithelial cells and influences proliferative injury in the glomerulus

Abstract: Glomerular parietal epithelial cells (PECs) are precursors to podocytes in mature glomeruli; however, as progenitors, the distinct intrinsic mechanisms that allow for repeated periods of cell-cycle arrest and re-entry of PECs after glomerulogenesis are unknown. Here, we show that the Src-suppressed protein kinase C substrate (SSeCKS), a multivalent scaffolding A kinase anchoring protein, sequesters cyclin D1 in the cytoplasm of quiescent PECs. SSeCKS expression is induced in embryonic PECs, but not in embryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 38 publications
5
30
0
Order By: Relevance
“…This “sequestration” phenomenon by A-Kinase Anchoring Proteins has been previously proposed in a study of AKAP79 overexpression in HEK293 cells [29]. Furthermore, gravin was shown to reduce FAK phosphorylation through the proposed sequestration of Src [30], and gravin has also been shown to sequester cyclin D1 away from the nucleus [31]. Our findings that PKA activity was reduced in the cytosol may be an important consequence of gravin expression or upregulation in vivo .…”
Section: Discussionsupporting
confidence: 77%
“…This “sequestration” phenomenon by A-Kinase Anchoring Proteins has been previously proposed in a study of AKAP79 overexpression in HEK293 cells [29]. Furthermore, gravin was shown to reduce FAK phosphorylation through the proposed sequestration of Src [30], and gravin has also been shown to sequester cyclin D1 away from the nucleus [31]. Our findings that PKA activity was reduced in the cytosol may be an important consequence of gravin expression or upregulation in vivo .…”
Section: Discussionsupporting
confidence: 77%
“…18 In our hands, anti-AKAP12 immunofluorescence staining resulted in strong immunostaining of human PECs and some tubular cells (Figure 7). A much weaker staining was observed in tubulointerstitial cells and endothelial cells of glomerular and peritubular capillaries ( Figure 7C).…”
Section: Detecting Pecs In Sclerotic Lesions By Using Akap12 or Anxa3supporting
confidence: 49%
“…We 21, 27 and others 3, 5, 2831 have reported that a subset of CD44 stained PECs, migrate from Bowman’s capsule to the glomerular tuft following podocyte injury. In the current study, PECs were identified by staining for PAX8 32 and SSeCKS.…”
Section: Resultsmentioning
confidence: 75%